Overproduction of single cell oil from xylose rich sugarcane bagasse hydrolysate by an engineered oleaginous yeast Rhodotorula mucilaginosa IIPL32. (15th October 2019) - Bandhu, Sheetal; Bansal, Neha; Dasgupta, Diptarka; Junghare, Vivek; Sidana, Arushdeep; Kalyan, Gazal; Hazra, Saugata; Ghosh, Debashish
Highlights: RMIIPL32 produced single cell oil using xylose fraction of sugarcane bagasse as a carbon source. Yeast oil satisfies ASTM D 6751, EN 14214 and IS 15607 biodiesel standards. Malic enzyme over expression by targeted genome integration improved oil production by 1.18 fold. Abstract: Rise in global fuel demands and approaching towards the 'peak-oil, ' liquid fuels from non-fossil resources are being considered as promising alternatives. Yeast single cell oil is gaining significant attention as feedstock for biofuels or oleochemicals over tree-borne or algal oil. In the present work, the oil-producing capacity of an oleaginous yeast Rhodotorula mucilaginosa IIPL32 has been enhanced to 1.18-fold by overexpressing the cytosolic malic enzyme through genome integration and cultivating the yeast on sugarcane bagasse derived xylose on 15 L fermenter scale. Detailed in silico modeling and docking study of the malic enzyme of R. mucilaginosa was also carried out to understand its interaction with cofactors involved in lipogenesis. Estimation of fuel properties revealed that the lipid produced by transformed yeast complies with fourteen out of the seventeen fuel properties in the EU, Indian and US standards. We conclude with the plausible use of the engineered yeast for industrial production of oil as an alternative to plant-borne oil for biofuel production in a lignocellulosic-biomass-based biorefinery.